Family Communication Patterns and Conflict Management Styles in an Animated Film (An evaluation of the film Mitchells vs. the Machines) - Lertsuwan, Benya; Paprach, Thapthep (Journal of Contemporary Issues in Media & Communication (JCIMC), 2022)
This study explores the concept of family communication patterns, conflict management styles in the context of an animated film (The Case of The Mitchells vs. the Machines). A self-administered questionnaire was used by the researchers. We assessed the family communication patterns and conflict management styles in an animated film using the Family Communication Patterns instrument (RFCP) which is used in the previous research by family counselors. The content analysis and diagnostic survey indicated that the Mitchells vs. the Machines, showed both low conformity orientation and conversation orientation. The fictional Mitchell family was of a laissez-faire family type. But there was variation between family members. In this context, it was also found that daughter Katie (the main character) adopted an integrating conflict management style with her family members. Concerning the relations between family communication patterns and conflict styles, Katie’s conflict management style which resulted in a “happily ever after conclusion” in which the parents completely changed conflict styles were not consistent with family communication patterns identified in previous research. It is in fact extremely difficult to change the family communication patterns of parents who after all created the patterns in the first place. As a family movie, thus, this fictional animated film provides a new opportunity understand why a good society starts at a smallest unit, even if it is not possible in real life.